وقفات فنية في شعر السميسر - دقالي د. محمد أحمد امبارك (Aljameai, 2022)
الملخص: يقف البحث على ملامح فنية من شعر السميسر ( خلف بن فرج الإلبيري ) الشاعر الأندلسي ، الشاعر الذي اشتهر بنقده السياسي لملوك الطوائف من خلال شعره ، وليس الغرض من هذه الدراسة تتبع حياة وموضوعات شعره إنما الوقوف على بعض الجوانب الفنية من خلال جانب البنية الإيقاعية والبنية اللغوية والأسلوبية . تناول البحث بعض الوقفات الفنية لنماذج من شعر السميسر من خلال اتباع المنهج الأسلوبي ، مع الإفادة من بعض المناهج الأخرى التي تقتضيها ضرورة الدراسة . فعلى صعيد البنية الإيقاعية يلاحظ الباحث أن مقطوعات الشاعر غنية بالظواهر اللفظية البديعية مثل : التجنيس ، ورد العجز على الصدر ، والسجع ، والتصريع . وقد حاولنا التركيز على إيقاعات هذه الألفاظ حسياً إلى جانب مستوياتها الدلالية باعتبارها تمثل أحد العناصر الأساسية في بناء النص الشعري . وكذلك إيقاعات المعنى التي جاءت في شعر السميسر المتمثلة في ظواهر ( التكرار والموازنة ، والتضاد ، والمقابلة ) وهي متولدة من إيقاع اللفظ ، فكثيرا ما تتداخل هذه العناصر الإيقاعية فيما بينها إسهاماً في سبك النص وتلاحمه ، ويتوافق وجودها مع ما يتطلبه السياق الدلالي للنص ويكون ارتباطها فيما بينها أشبه بالقطع الداخلية لمحرك السيارة تغذي بعضها بعضاً ، وتكون الإيقاعات الخارجية بمثابة القطع الخارجية التي تساعد على تشغيل المحرك ، وتكتمل عملية التشكيل البنائي للنص مع البناء الدلالي بغية الوصول إلى مغزى النص وتأثيره في المتلقي . وتبرز الثنائيات الضدية في بناء النص إيقاعياُ ودلالياً من خلال بروز أساليب الخبر والإنشاء في شعر السميسر ، والمتداخلة فيما بينها، وقد لعب عنصر المقابلة دوراً كبيراً في تفاعل هذه الأساليب التي خرجت عن دلالاتها الحرفية ووظفت في سياق تجربة الشاعر . وهكذا فهذا النسيج اللغوي المتفاعل إيقاعياً ودلالياً بعناصره المختلفة أكسب النص طابع النقد السياسي الذي أوحت به تلك الثنائية الضدية التي تشكلت من خلال الدوال المختلفة . Abstract: The research stands on the artistic features of the poetry of Al-Samisar (Khalaf bin Faraj Al-Ilbiri), the Andalusian poet, the poet who is famous for his political criticism of the kings of the sects through his poetry. and stylistics. The research dealt with some technical pauses for examples of Samiser’s poetry by following the stylistic approach, with the benefit of some other approaches required by the necessity of the study. On the level of the rhythmic structure, the researcher notes that the poet’s pieces are rich in inventive verbal phenomena, such as: naturalization, restitution of disability on the chest, assonance, and al-Tari. We have tried to focus on the sensual rhythms of these words as well as their semantic levels, as they represent one of the basic elements in building a poetic text. As well as the rhythms of meaning that came in the poetry of Samiser represented in the phenomena (repetition, equilibrium, contrast, and interview) which are generated from the rhythm of the pronunciation. Among them, they are like the internal parts of the car engine feeding each other, and the external rhythms are the external parts that help the engine run, and the process of structural formation of the text is completed with the semantic structure in order to reach the meaning of the text and its impact on the recipient. The opposite dichotomies emerge in the construction of the text, both rhythmically and semanticly, through the emergence of the methods of news and construction in the poetry of Al-Samisir, and the overlapping among them. The interview element played a major role in the interaction of these methods, which departed from their literal connotations and were employed in the context of the poet’s experience. Thus, this linguistic fabric that interacts rhythmically and semanticly with its various elements has given the text the character of political criticism, which was inspired by that opposing duality that was formed through the various signs.